Haemoglobinopathies: A Retrospective Study from a Tertiary Care Centre, Southern India - Hemalata Lokanatha; Pradeep Rudramurthy (National Journal of Laboratory Medicine, 2022)
Introduction: Thalassaemia and other structural haemoglobinopathies are the major genetic disorders that cause significant morbidity in children. Haemoglobinopathies need to be diagnosed at the earliest in order to offer suitable treatment, carrier identification and counselling which will help to decrease the incidence of haemoglobinopathies. Aim: To study the clinicohaematological spectrum of children with thalassaemia and other haemoglobinopathies, followed by family screening and counselling. Materials and Methods: This retrospective cross-sectional study was taken up at Department of Pathology, Indira Gandhi Institute of Child Health, Bangalore, Karnataka, India from January 2018 to December 2020, during which records of 235 cases were studied, out of which 100 were the children visiting Institute and 135 were the parents and siblings of these children. Diagnosis of these cases was followed by counselling for these families. Results were calculated by data analysis. Percentages were calculated from the frequency of the variables. Results: Amongst the records of 235 cases studied, β-thalassaemia major was the most common haemoglobinopathy found in 75 patients, followed by sickle cell anaemia in 10 patients. β-thalassaemia trait was the most common haemoglobinopathy among the parents of these children, which was found in 125 individuals. Conclusion: β-thalassaemia major is the most common disorder amongst the children with haemoglobinopathy, followed by sickle cell anaemia. β-thalassaemia trait is a common entity amongst the carriers of haemoglobinopathy.